Measuring 3D growth plate shape: Methodology and application to cam morphology. Issue 11 (10th January 2021) - Horenstein, Rachel E.; Meslier, Quentin; Spada, Julia A.; Halverstadt, Anne; Lewis, Cara L.; Gimpel, Mo; Birchall, Richard; Wedatilake, Thamindu; Fernquest, Scott; Palmer, Antony; Glyn‐Jones, Siôn; Shefelbine, Sandra J.
Abstract: Physeal changes corresponding to cam morphology are currently measured using two‐dimensional (2D) methods. These methods are limited by definitions of the femoral neck axis and head center that are dependent on the radiographic plane of view. To address these limitations, we developed three‐dimensional (3D) methods for analyzing continuous growth plate shape using magnetic resonance imaging scans. These new methods rely on a single definition of the femoral neck axis and head center that are both nondependent on the radiographic plane of view and allow for analysis of growth plate shape across the growth plate surface (performed using statistical parametric mapping). Using our 3D method, we analyzed the position of the growth plate in the femoral head (relative to a plane tangent to the femoral head) and the curvature of the growth plate (relative to a plane through the center of the growth plate) in 9–16‐year‐old males at risk for cam morphology and their recreationally active peers ( n = 17/cohort). These two measurements provide an avenue to separately analyze the effects of these variables in the overall growth plate shape. We detected differences in growth plate shape with age in recreationally active adolescents but did not detect differences between at risk and recreationally adolescents.